Evolutionary concepts in immunology - Jack, Robert (Springer, 2019)
Immunology is a nodal subject that links many areas of biology. It permeates the biosciences, and also plays crucial roles in diagnosis and therapy in areas of clinical medicine ranging from the control of infectious and autoimmune diseases to tumour therapy. Monoclonal antibodies and small molecule modulators of immunity are major factors in the pharmaceutical industry and now constitute a multi billion dollar business. Students in these diverse areas are frequently daunted by the complexity of immunology and the astonishing array of unusual mechanisms that go to make it up.Starting from Dobzhansky’s famous slogan, "Nothing in biology makes sense except in the light of evolution", this book will serve to illuminate how evolutionary forces shaped immunity and thus provide an explanation for how many of its counter intuitive oddities arose. By doing so it will provide a conceptual framework on which students may organise the rapidly growing flood of immunological knowledge